Evidence Provided by the Literature on the Use of Crossfit Elements in Sport - C. Stanciu; V. Ene-Voiculescu (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics, 2024)
In recent years, scientific literature has increasingly examined the use of CrossFit in various sports. This paper aims to analyze this literature through bibliometric methods. Searches in the Scopus database from 2000 to January 30, 2024, yielded 567 relevant results. The analysis identified publication dates, prominent authors, affiliations, and key publications, aligning findings with UN goals. Around 75% of articles were published in the last 5 years, indicating rising interest. Results were categorized into sports branches, performance measurement, injuries, nutrition, motivation, and benefits